Morphine Binds Creatine Kinase B and Inhibits Its Activity - Weinsanto, Ivan; Mouheiche, Jinane; Laux-Biehlmann, Alexis; Delalande, François; Marquette, Arnaud; Chavant, Virginie; Gabel, Florian; Cianferani, Sarah; Charlet, Alexandre; Parat, Marie-Odile; Goumon, Yannick (Frontiers in Cellular Neuroscience, 2018)
Morphine is an analgesic alkaloid used to relieve severe pain, and irreversible binding of morphine to specific unknown proteins has been previously observed. In the brain, changes in the expression of energy metabolism enzymes contribute to behavioural abnormalities during chronic morphine treatment. Creatine kinase B (CK-B) is a key enzyme involved in brain energy metabolism. CK-B also corresponds to the imidazoline-binding protein I2 which binds dopamine (a precursor of morphine biosynthesis) irreversibly. Using biochemical approaches, we show that recombinant mouse CK-B possesses a µM affinity for morphine and binds to morphine in vitro. The complex formed by CK-B and morphine is resistant to detergents, reducing agents, heat treatment and SDS-polyacrylamide gel electrophoresis (SDS-PAGE). CK-B-derived peptides CK-B1-75 and CK-B184-258 were identified as two specific morphine binding-sites. In vitro, morphine (1-100 μM) significantly reduces recombinant CK-B enzymatic activity. Accordingly, in vivo morphine administration (7.5 mg/kg, i.p.) to mice significantly decreased brain extract CK-B activity compared to saline-treated animals. Together, these results show that morphine strongly binds CK-B and inhibits its activity in vitro and in vivo.